Ateist ve Deistlerin Din Algısı: Üniversite Öğrencileri Üzerine Psiko-Sosyolojik Bir Araştırma / Approachs of Atheists and Deists to Religion: A Psycho-Sociological Research on University Students - Zavalsız, Yusuf Sinan; Şahin, Ensar (Journal of History Culture and Art Research, 2018)
Abstract This study deals with changing views and attitudes of individuals towards creator and religion. Apart from this, we analyzed the reasons behind the change of opinions. In this paper, we also investigated in a psychosocial approach what lies in the background of that through which atheists and deists adopted this understanding. After we briefly explained the terms "atheism" and "deism" we inquired about the family relations of respondents beginning from their childhood and puberty ages. We asked the respondents whether they are informed by families and the frequency of their practising the duties of past religious affiliates which is followed by sceptical manner about the religion adhered questioning if they experienced any traumatic event and examined the circumstances that motivated them to be atheists or deists. We also sought to determine similarities and differences between atheists and deists in terms of the way of thinking. This research has been prepared within the frame of the interviews carried out with 25 volunteers, 15 of whom were atheists and 10 deists. Some of the interviews were recorded their consent having been obtained. As per the right of privacy and the request of the subjects, their universities, identity and personal information have been kept confidential. Nevertheless, they have been given nicknames to be used exclusively in this research. Öz Araştırmamız, Ateist ve Deistlerin Din Algısı: Üniversite Öğrencileri Üzerine Psiko-Sosyolojik Bir Araştırma başlığı altında, bireylerin, yaratıcı ve din konusunda değişen düşüncelerini ele almaktadır. Düşünce değişikliğinin arka planında hangi kodların bulunduğu ayrıca irdelenmeye çalışılmıştır. Bu çalışmada ateist ve deistlerin, arka planda ateizmi ve deizmi benimsemesine yol açan sebeplerin neler olduğu psiko-sosyal bir bakış açısıyla incelenecektir. Ateizm ve deizmin ne olduğu kısaca izah edildikten sonra deneklerin çocukluk ve ergenlik döneminden başlanarak aile ilişkileri ele alınmıştır. Dinî konularda ailesi tarafından bilgilendirilme durumu, toplumla ilişkileri, daha önce mensup olduğu dinin ibadetlerini yerine getirip getirmeme sıklığı sorulmuştur. Sonrasında mensup olunan dine dair taşınan şüpheler, hayatlarını etkileyen travmatik bir olay yaşayıp yaşamadıkları, onları ateist veya deist olmaya iten faktörler irdelenmiştir. Ateist ve deistlerin birbirinden ayrıldığı ve benzer düşündüğü konular ortaya çıkartılmaya çalışılmıştır. Araştırma, 15’i ateist, 10’u deist, toplam 25 gönüllü öğrenci ile gerçekleştirilen mülakatlar çerçevesinde ortaya çıkmıştır. Mülakatlarda, isteğe bağlı olarak ses kaydı alınmıştır. Özel hayatın gizliliği ilkesince ve deneklerin talepleri doğrultusunda, üniversiteleri, kimlik bilgileri ve isimleri gizli tutulmuş, yalnız bu çalışmada kullanılmak üzere kendilerine takma isim verilmiştir.